Effect of Surface-Charged Poly(methyl Methacrylate) on the Adhesion of Candida Albicans - Sang E. Park, DDS, MMSc,1 Antony Raj Periathamby, PhD,2 and (Journal of Prosthodontics, 2003)
The aim of this study was to investigate the ability of a new surface-modified denture resin to reduce adhesion of Candida albicans to the denture surface